Crossing the Bridge to Leadership: Exposing Ambition Among Challenges - Cunneen, Mary Elizabeth (Frontiers in Education, 2021)
Teaching is a profession dominated by women. Principalship, on the other hand, is an arena populated by men. This study, which reports from the Republic of Ireland, reveals the challenges and opportunities encountered by ten women, from a cross section of school type and contexts, as they pursued a path to principalship. The nature of their personal contexts in addition to career ambitions formed in some cases earlier, in others later, in their teaching lives, acted as informants along their professional trajectories. Leadership is identified as a male prerogative, thereby providing additional hurdles for women as they cross the bridge to an arena that operates cultural climates conducive to male working practices. The women, in this study, articulated how national culture, organisational practices and personal obligations all acted in tandem to assist or hinder in configuring their labyrinthine career aspirations.